Effectiveness of Saikokaryukotsuboreito (Herbal Medicine) for Antipsychotic-Induced Sexual Dysfunction in Male Patients with Schizophrenia: A Description of Two Cases. (27th January 2014) - Takashi, Tsuboi; Uchida, Hiroyuki; Suzuki, Takefumi; Mimura, Masaru
Abstract : Antipsychotics sometimes cause sexual dysfunction in people with schizophrenia. The authors report the effectiveness of Saikokaryukotsuboreito (Japanese traditional herbal medicine, Chai-Hu-Jia-Long-Gu-Mu-Li-Tang in Chinese) for antipsychotic-induced sexual dysfunction in two male patients with schizophrenia. The first patient was a 28-year-old man with schizophrenia who suffered erectile dysfunction induced by olanzapine 10 mg/day; the erectile dysfunction significantly improved following the treatment of Saikokaryukotsuboreito 7.5 g/day. The other case was a 43-year-old man with schizophrenia who was receiving fluphenazine decanoate at 50 mg/month and had difficulties in ejaculation; add-on of Saikokaryukotsuboreito 7.5 g/day recovered his ejaculatory function. There has been no report on the effectiveness of Japanese herbal medicine formulations for antipsychotic-induced sexual dysfunction. Although the effectiveness of Saikokaryukotsuboreito needs to be tested in systematic clinical trials, this herbal medicine may be a treatment option to consider for this annoying side effect.